Templates for Activism: Creative Convergences in Feminist Art and Law - Peters, Sheryl (Atlantis)

(untitled) (Mount Saint Vincent University, 2006)
Community arts are an underexamined approach to creative social advocacy that catalyzes a shift in perceptions about social issues through cultural, symbolic and artistic means. One example, Templates for Activism, forges new geographies between feminist jurisprudence, feminist art and community arts practices, and in doing so seeks new ways to foster the work of feminist law.